Ornamental Program Area Research Planning and Prioritization - Flordeliza Lantican (Philippine Institute for Development Studies (PIDS), 2000)
The Philippine cutflower industry has evolved from a garden hobby to commercial enterprise only in the early 1980s. The production of fresh cutflowers is intended primarily to cater to the domestic market. As the preference and buying capacity of high and middle class consumers have changed and improved, domestic requirement has grown so fast in tandem with institutional demand brought about by the growing tourism industry. At present, only a limited quantity of locally produced cutflowers is traded in the international market. The countrys proximity to major international markets coupled with a favorable agro-climatic conditions and low-labor costs serve as potential basis for an export-oriented development of the industry. Under the DAs Key Commercial Crops Development Program (KCCDP), cutflowers are among the commodities that require more government investments on marketing strategy or promotion, product development/awareness and extensive research to boost their competitiveness in the medium-term. As an emerging export winner, DOST has included ornamental horticulture as one of the priority commodities for science and technology agenda (STAND). Both government initiatives were conceived to address the industrys limitations in terms of production/propagation, pest management, and postharvest handling. This study aims to present an industry profile with focus on domestic production, consumption, external trade, problems/constraints, and market prospects; review past researches on ornamentals, technologies generated/adopted, and the extent of participation of the private and public sectors; identify research and technology gaps for the ornamental industry; identify strengths and weaknesses in the institutional structure of research and extension interface, including physical and manpower investments and research complementation efforts; and suggest recommendations and R&D agenda for the ornamental industry to be used by DA-BAR in research planning and prioritization.
Keywords: 330; cutflower industry; ornamentals